Amos Oz : The Legacy of a Writer in Israel and Beyond. - Omer-Sherman, Ranen (Ann Arbor : State University of New York Press, 2023)
Explores the writer's enduring literary and political legacy.
Chapter Seventeen: Of Howling Jackals and Village Scenes: A Lament -- Notes -- Chapter Eighteen: Exultation, Disillusionment, and Late Inspiration: Oz's Once and Future Kibbutz -- Notes -- Chapter Nineteen: From Tragedy to Betrayal: Judas and the Subversive Politics of Oz's Last Act -- Introduction -- Tragedy -- Betrayal -- Historicity -- Uchronia -- Notes -- Works Cited -- Afterword: About My Father -- Note -- Contributors -- Editor -- Contributors -- Further Reading: Critical Resources in English -- Books -- Essays, Articles, and Interviews -- Films -- Index
Description based upon print version of record.
Includes bibliographical references.
JSTOR
Keywords: Oz, Amos, -- 1939-2018 -- Influence; Oz, Amos, -- 1939-2018 -- Criticism and interpretation; Oz, Amos, -- 1939-2018; Israeli literature -- History and criticism; Israeli literature -- Political aspects; Littérature israélienne -- Histoire et critique; Littérature israélienne -- Aspect politique; LITERARY CRITICISM / Jewish; Influence (Literary, artistic, etc.); Israeli literature; Israeli literature -- Political aspects; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.